ASN Employees: Instruction, Communication, Coordination and Work Results - Teguh Andang Buana; Mohamad Rifaldy; Khaerudin Imawan; Dedet Erawati (Pelopor Publikasi Akademika, 2024)
An employee's performance is determined by how well they achieve the goals and criteria set by the organization or company they work for. In addition, employee performance consists of the results achieved by an employee in carrying out his or her obligations and responsibilities in the organization. The purpose of the study is to find out and analyze the extent to which communication has an impact on the effectiveness of employee work, and to find out and analyze the extent to which infrastructure facilities affect the effectiveness of employee work. The researchers used a qualitative descriptive methodology. The results of the study used organizational communication theory cited by Max Weber. The efficacy of internal communication has an impact on improving employee performance at the Cirebon City Hall Secretariat Office, based on the findings of this study. So it can be concluded that effective internal communication can build cooperation towards the achievement of company goals.